Multiquery motion planning in uncertain spaces: Incremental adaptive randomized roadmaps - Khaksar, Weria; Uddin, Md Zia; Torresen, Jim (Zielona Góra: Uniwersytet Zielonogórski)
Sampling-based motion planning is a powerful tool in solving the motion planning problem for a variety of different robotic platforms. As its application domains grow, more complicated planning problems arise that challenge the functionality of these planners. One of the main challenges in the implementation of a sampling-based planner is its weak performance when reacting to uncertainty in robot motion, obstacles motion, and sensing noise.
Keywords: motion planning; uncertainty; roadmaps; sampling; obstacle avoidance